Gas-discharge visualization method in sport bioelectrography - Korotkov, K. G.; Korotkova, A. K. (Theory and Practice of Physical Culture, 2018)
The article analyzes the history of the gas-discharge visualization method application in sports since the pioneering studies by Professor P.V. Bundzen in the late 1990s that showed benefits of the gas-discharge visualization method for the psycho-physiological performance and competitive fitness tests. The multiannual studies since then demonstrated benefits of the method for the competitive conditioning and forecasts as verified by the practical application experience of the Russian Paralympians. The 20-year-long practical experience of the gas-discharge visualization method application has been successful as verified by the psycho-physiological performance and competitive fitness tests and forecasts. For the last few years the gas-discharge visualization method has been increasingly and successfully applied in trainings of the Russian national Paralympic and Olympic teams. The method is being actively used in the US, Spain, Malaysia, Belorussia and Ukraine, with the Saint Petersburg Scientific Research Institute of Physical Culture analysts providing necessary consulting and practical support to the users.